Atomic habits - Clear, James (New York : Avery, an imprint of Penguin Random House, 2018)
James Clear, an expert on habit formation, reveals practical strategies that will teach you how to form good habits, break bad ones, and master the tiny behaviors that lead to remarkable results. He draws on proven ideas from biology, psychology, and neuroscience to create an easy-to-understand guide for making good habits inevitable and bad habits impossible.
"No matter your goals, Atomic Habits offers a proven framework for improving-every day. James Clear, one of the world's leading experts on habit formation, reveals practical strategies that will teach you exactly how to form good habits, break bad ones, and master the tiny behaviors that lead to remarkable results. If you're having trouble changing your habits, the problem isn't you. The problem is your system. Bad habits repeat themselves again and again not because you don't want to change, but because you have the wrong system for change. You do not rise to the level of your goals. You fall to the level of your systems. Here, you'll get a proven system that can take you to new heights. Clear is known for his ability to distill complex topics into simple behaviors that can be easily applied to daily life and work. Here, he draws on the most proven ideas from biology, psychology, and neuroscience to create an easy-to-understand guide for making good habits inevitable and bad habits impossible. Along the way, readers will be inspired and entertained with true stories from Olympic gold medalists, award-winning artists, business leaders, life-saving physicians, and star comedians who have used the science of small habits to master their craft and vault to the top of their field. Learn how to: make time for new habits (even when life gets crazy); overcome a lack of motivation and willpower; design your environment to make success easier; get back on track when you fall off course; and much more. Atomic Habits will reshape the way you think about progress and success, and give you the tools and strategies you need to transform your habits-whether you are a team looking to win a championship, an organization hoping to redefine an industry, or simply an individual who wishes to quit smoking, lose weight, reduce stress, or achieve any other goal." --
Introduction : My story -- The fundamentals: why tiny changes make a big difference : The surprising power of atomic habits ; How your habits shape your identity (and vice versa) ; How to build better habits in 4 simple steps -- The 1st law: Make it obvious : The man who didn't look right ; The best way to start a new habit ; Motivation is overrated: environment often matters more ; The secret to self-control -- The 2nd law: Make it attractive : How to make a habit irresistible ; The role of family and friends in shaping your habits ; How to find and fix the causes of your bad habits -- The 3rd law: Make it easy : Walk slowly, but never backward ; The law of least effort ; How to stop procrastinating by using the two-minute rule ; How to make good habits inevitable and bad habits impossible -- The 4th law: Make it satisfying : The cardinal rule of behavior change ; How to stick with good habits every day ; How an accountability partner can change everything -- Advanced tactics: how to go from being merely good to being truly great : The truth about talent (when genes matter and when they don't) ; The Goldilocks rule: how to stay motivated in life and work ; The downside of creating good habits -- Conclusion : The secret to results that last -- Appendix : What should you read next? ; Little lessons from the four laws ; How to apply these ideas to business ; How to apply these ideas to parenting.
Includes bibliographical references (pages 273-298) and index
Online resource; title from epub title page (ProQuest Ebook Central, viewed February 18, 2021).
Keywords: Habit; Habit breaking; Behavior modification; Habits; Behavior Therapy; Habitude; Mauvaises habitudes; Modification du comportement; BUSINESS & ECONOMICS -- Organizational Behavior; PSYCHOLOGY -- Social Psychology; SELF-HELP -- Personal Growth -- General; FAMILY & RELATIONSHIPS -- Life Stages -- General; PSYCHOLOGY -- Developmental -- General; PSYCHOLOGY -- Developmental -- Lifespan Development; PSYCHOLOGY -- General; Behavior modification; Habit; Habit breaking; Self-help publications; Self-help publications; Livres de croissance personnelle